A Review of Oxygen Use During Chest Compressions in Newborns-A Meta-Analysis of Animal Data - Catalina Garcia-Hidalgo; Catalina Garcia-Hidalgo; Po-Yin Cheung; Po-Yin Cheung; Anne Lee Solevåg; Maximo Vento; Maximo Vento; Maximo Vento; Megan O'Reilly; Megan O'Reilly; Ola Saugstad; Georg M. Schmölzer; et al. (Frontiers Media S.A., 2018)
Background: International consensus statements for resuscitation of newborn infants recommend provision of 100% oxygen once chest compressions are required. However, 100% oxygen exacerbates reperfusion injury and reduces cerebral perfusion in newborn babies.Objective: We aimed to establish whether resuscitation with air during chest compression is feasible and safe in newborn infants compared with 100% oxygen.Methods: Systematic search of PubMed, Google Scholar and CINAHL for articles examining variable oxygen concentrations during chest compressions in term newborns.Results: Overall, no human studies but eight animal studies (n = 323 animals) comparing various oxygen concentrations during chest compression were identified. The pooled analysis showed no difference in mortality rates for animals resuscitated with air vs. 100% oxygen (risk ratio 1.04 [0.35, 3.08], I2 = 0%, p = 0.94). ROSC was also similar between groups with a mean difference of −3.8 [−29.7-22] s, I2 = 0%, p = 0.77. No difference in oxygen damage or adverse events were identified between groups.Conclusions: Air had similar time to ROSC and mortality as 100% oxygen during neonatal chest compression. A large randomized controlled clinical trial comparing air vs. 100% oxygen during neonatal chest compression is warranted.